Pratiques de l’écrit et temporalités dans le travail domestique de jeunes mères - Jean-Pierre Mercier (Éducation et Socialisation)
Household work can be seen as part of care practices. It is woven by many social literacy practices. An ethnographic case study has allowed to document literacy practices for household work done by young mothers (n =31). These women articulate these practices to different temporalities : the temporality of the present moment or the one of the future moment, namely a register of planed events and one of anticipated future. The goal of this article is to present these practices and these temporalities. Results help to understand the realities these women back to training in Ma place au soleil live. Ma place au soleil is a Quebec programme that supports training as well as social and professional integration of young parents without highschool diploma. Results also help to understand how these women conciliate household work and school work.